Situated Meaning in Patricia McCormick’s Novel Cut - Subedi, Bhim Prasad (The Saraswati Review, 2024)
The present article investigates the idea of situated meaning in Patricia McCormick's Novel Cut. This study explores the complex interactions between language, context, and interpretation through a thorough reading of the text, providing insight into the process of creating and navigating meaning within certain situational framework. The research examines the contextual relevance of conversation, narrative components, and character interactions, shedding light on the complex ways in which language and context interact to influence reader comprehension. It does this by drawing on theories of discourse analysis and literary criticism. This study sheds light on the intricate ways that psychological dynamics, social elements, and narrative techniques play a part in meaning-making inside McCormick's gripping story universe.